One Billion Euro Program for Early Childcare Services in Italy - Isabella Giorgetti; Matteo Picchio (Institute of Labor Economics (IZA), 2018)
In 2007 the Italian central government started a program by transferring funds to regional governments to develop both private and public early childcare services. Exploiting the different timing of program implementation across regions, we evaluate its effectiveness in boosting the public supply of early childhood educational services. We find that the ratio between the available slots in public early childhood education and the population of those aged 0-2 increased by 18.1% three years after the start of the program, with respect to the pre-program level. The program impact was however nil in the South and totally driven by the Center-North.
Keywords: C23; H52; H70; J13; R10; 330; early childcare services; public early childhood education; government transfers; difference-in-differences